Effect of Fuel Oil - Gasoline Fusel Blends on the Performance and Emission Characteristics of Spark Ignition Engine: A Review - Awad, Omar I.; R., Mamat; Obed M., Ali; I. M., Yusri (JSRAD, 2016)
Alcohol-based as alternative fuels attract the attention of many researchers. Many kinds of research have been conducted on performance, combustion and emission characteristics of alcohol utilized in spark ignition engines. Fusel oil is an alcohol based fuel obtained as a by-product of alcohol fermentation from agricultural such as beet, cone, potatoes, rice, etc. The calorific value, higher evaporation heat and octane number of fuel oil close to other alternative fuels. Despite that, there is limited number of studies refer on the usage of fusel oil as fuel in spark ignition engines. This paper reviews the works done ‘effects of fusel oil as a fuel blends on performance (brake torque, brake power, BSFC, effective efficiency, EGT) and emissions (CO, NOx, HC) characteristics in spark ignition engine. It was seen that when fusel oil – gasoline blend used at almost the engine torque and specific fuel consumption increased, Also HC and CO emissions averagely increased. Furthermore knocking and nitrogen oxides NOx were decreased .Moreover volumetric efficiency and octane number increases with the increase in percentage of fusel oil in blend tests. In other hand the negative effects that happened in engine performance caused by the higher water content in fusel oil.